Higher order nuclear organization: three-dimensional distribution of small nuclear ribonucleoprotein particles. - Spector, D L (1990)
The structural and functional organization of the cell nucleus has been investigated using three-dimensional reconstruction, immunoelectron microscopy, and high-resolution in situ autoradiography. Nuclear regions enriched in small nuclear ribonucleoprotein particles (snRNPs) form a reticular network within the nucleoplasm that extends between the nucleolar surface and the nuclear envelope. The snRNPs occupy approximately 18% of the volume of CHOC 400 cell nuclei. The in situ sites of DNA replication and transcription are complementary to, rather than coincident with, the nuclear regions concentrated in snRNPs. Based on these data a three-dimensional model of the organization of the mammalian cell nucleus is presented.